2013
DOI: 10.3109/02656736.2012.758875
|View full text |Cite
|
Sign up to set email alerts
|

Antiparasitic effects of gold nanoparticles with microwave radiation on promastigotes and amastigotes ofLeishmania major

Abstract: Thermotherapy using MW radiation in the presence of GNPs may be proposed as a new approach to treat leishmaniasis in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…In previous years, several kinds of nanoparticles have been proposed as anti-parasite agent [1,16,24]. With respect to increase in resistance to existing anthelmintic, there is an urgent need to investigate novel strategies for control of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…In previous years, several kinds of nanoparticles have been proposed as anti-parasite agent [1,16,24]. With respect to increase in resistance to existing anthelmintic, there is an urgent need to investigate novel strategies for control of parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The high extinction coefficient of radiation by the GNPs which is due to the coherent oscillations of electrons in gold metal is intensified by inducing RF radiation (18-20). This phenomenon can be used in various applications such as hyperthermia of RCC (21). It should be noted that, for healthy tissues, the toxicity of GNPs can be determined by size, shape, surface charge, and surface coating, however, the overall toxicity dose of GNPs is in an acceptable level (17).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that thermotherapy using microwave radiation in synergism with GNPs may be proposed as a new approach to treat leishmaniasis in future studies (21). Moreover, magnetic nanoparticles (MNPs) have been employed as a potent device in numerous biological and medical investigations (22).…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous leishmaniasis (CL) is a parasitic disease caused by various species of Leishmania such as Leishmania major (L. major). This disease is transmittable to humans by the female sandfly of Phlebotomus species [Sazgarnia et al, ]. L. major begins its lifecycle in the gut of the sandfly; these parasites transform from aflagellated amastigotes into flagellated promastigotes for 1–2 weeks.…”
Section: Introductionmentioning
confidence: 99%